Impact of water pollution on human health in the Central African Republic - Kamba, Francklin; Sangija, Frank; Wei, Shiqiang (Advances in Social Sciences Research Journal, 2016)
Bacterial contamination of waters and their impacts on human health in the Central African Republic is a pollution problem that goes far back in time. Today, water quality is impaired, including the contamination of fecal microorganisms, excessive use of agrochemicals, uncontrolled discharges from industries and solid and liquid waste from households and municipal. Most of people in Central Africa use water directly from the wells and rivers water for their domestic activities include drinking. These works highlight the bacteriological and nitrate pollution of surface and groundwater streams and how can impair public health. Many reports concluded that this pollution came from poor sanitation wastes/extracts. Other studies have revealed the presence of nitrates and coliform bacteria in groundwater in agricultural areas it concludes that, this pollution comes from the reuse of untreated wastewater in agriculture. Rivers and lakes seem to be most contaminated sources because are most exposed to waste. Human activities and poor municipal waste control contribute to water pollution and results to serious health problems. Main data in this review study are collected in various existing studies by many researchers and published in international and national journals, but also by non-governmental organizations and the Central African Government reports.